2015
DOI: 10.5539/gjhs.v7n4p295
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Case-Based Team Learning on Students' Learning, Self Regulation and Self Direction

Abstract: Introduction:The application of the best approaches to teach adults in medical education is important in the process of training learners to become and remain effective health care providers.This research aims at designing and integrating two approaches, namely team teaching and case study and tries to examine the consequences of these approaches on learning, self regulation and self direction of nursing students.Material & Methods:This is aquasi experimental study of 40 students who were taking a course on me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 30 publications
2
22
0
4
Order By: Relevance
“…Our study confirmed previously published outcomes of enhanced engagement and satisfaction with learning activities, increased selfdirected learning, and high acceptance rate of TBL compared to traditional lectures (Sisk 2011;Rezaee and Mosalanejad 2015). Prior resident exposure to TBL was highly variable and did not seem to affect the outcomes and acceptance rate of TBL.…”
Section: Discussionsupporting
confidence: 80%
“…Our study confirmed previously published outcomes of enhanced engagement and satisfaction with learning activities, increased selfdirected learning, and high acceptance rate of TBL compared to traditional lectures (Sisk 2011;Rezaee and Mosalanejad 2015). Prior resident exposure to TBL was highly variable and did not seem to affect the outcomes and acceptance rate of TBL.…”
Section: Discussionsupporting
confidence: 80%
“…19 The SDLRS is a scale that was used to assess the degree to which people considered themselves as having the skills and attitude essential for self-directed learning. Many studies report that it has good reliability and validity, 8,16,20 but several others cast on the cost and criticize its intent. 16,21,22 This scale is a 41-item questionnaire in five parts.…”
Section: Introductionmentioning
confidence: 99%
“…This particular approach originates from psychology and was developed by Vygotsky [8]. It contains three central ideas, which may be deemed the pillars of Vygotsky's [8] thought and are the following: (1) psychological functions have a biological base, because they are products of cerebral activity; (2) psychological functioning is founded on the social relationships between the individual and the external world and develops as a historical process; (3) symbolic systems are the mediators of the human-world relationship [9].…”
Section: The Group Interrelational Methodsmentioning
confidence: 99%